Structural and Electromagnetic Wave Absorption Properties of Fe3O4NPs/rGO Composite Synthesized From Natural Materials - Husain, Husain; Adi, W. A.; Subaer, S.; Taryana, Y.; Putri, S. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
This study analyzes the structural and electromagnetic wave absorption properties of Fe3O4 nanoparticles (Fe3O4NPs) composite reinforced with reduced graphene oxide (rGO), synthesized from natural materials. The synthesis process involves the extraction of Fe3O4 from natural iron sources and the reduction of graphene oxide derived from biomass. Structural characterization was conducted using transmission electron microscopy (TEM) to confirm the formation and morphology of the Fe3O4NPs/rGO composite. Electromagnetic wave absorption properties were measured using a vector network analyzer (VNA) in the 8–12 GHz (X-band). The results show that the Fe3O4NPs/rGO composite exhibits excellent electromagnetic wave absorption with a minimum reflection loss value of -4 dB at a thickness of 2 mm. These findings highlight the potential of utilizing natural materials in developing efficient electromagnetic wave absorbers, contributing to advancements in sustainable material science.